Comparison of hepatotoxicity of tegoprazan, a novel potassium-competitive acid blocker, with proton pump inhibitors using real-world data: A nationwide cohort study - Kim, Min-Gul; Im, Yong-Jin; Lee, Jong-Hwan; Kim, Eun-Young; Yeom, Sang Woo; Kim, Jong Seung (Frontiers in Medicine, 2023)
Background Proton pump inhibitors (PPIs) are acid suppressants that are frequently prescribed in many countries to reduce heartburn. A potassium-competitive acid blocker (P-CAB; tegoprazan) was launched relatively recently that also inhibits gastric acid secretion. This study aimed to compare the hepatotoxicity of the six existing PPIs with P-CAB. Methods This retrospective cohort study was conducted between January 2019 and December 2020 and included data from the total population of 50 million inhabitants in Korea. Propensity score (PS) matching was performed using 10 variables, and the differences in hepatotoxicity between P-CAB and the six PPIs were compared in a similar distribution. The primary endpoint was hepatotoxicity which included toxic liver disease, hepatitis, hepatic failure, liver transplantation, and other liver diseases. Results The risk ratios (RR) of tegoprazan vs. the six PPIs (dexlansoprazole, esomeprazole, lansoprazole, omeprazole, pantoprazole, and rabeprazole) were all significant [RR: 0.70 (95% CI: 0.69–0.72), 0.81 (95% CI: 0.79–0.83), 0.61 (95% CI: 0.59–0.63), 1.17 (95% CI: 1.13–1.20), 0.61 (95% CI: 0.59–0.62), and 0.73 (95% CI: 0.71–0.75), respectively]. The risk ratio of tegoprazan vs. the six existing PPIs was 0.73 (95% CI: 0.72–0.75). The hazard ratios (HRs) of hepatotoxicity of the six PPIs to tegoprazan showed significantly higher values apart from omeprazole (HR: dexlansoprazole, 1.13; esomeprazole, 1.04; lansoprazole, 1.25; omeprazole, 0.77; pantoprazole, 1.26; rabeprazole, 1.15, respectively, and the six existing PPIs, 1.10). Conclusion Using a large-scale data cohort analysis consisting of 50 million Koreans, tegoprazan did not induce higher hepatotoxicity compared with the six conventional PPIs.